Development and challenges between supranational strategies and national traditions - the view from the UK - James Relly, Susan [Verfasser]; Keep, Ewart [Verfasser] (My University, 2020)
"The United Kingdom and the European Union's relationship around education and vocational education and training has been fraught. While many activities and initiatives from the EU were considered in the UK, only a few really ever took hold such as ERASMUS. Differing philosophical viewpoints about the nature and role of the nation state and concepts such as citizenship made cooperation and arrival at a common view problematic. This article draws together policy documents and research to show how the challenges between supranational strategies and national traditions ran counter to any real development around education and vocational education policy. The UK, when confronted with EU skills policies, individual schemes and programmes with a clearly defined purpose, particularly those delivering material benefits to UK participants, were seen positively. Supranational policy formation was not given the same priority and was undermined by a variety of factors including (but not limited to) English exceptionalism, and a national press and political class that subscribed to a deep scepticism concerning increased European integration and consequent diminution of national sovereignty. Educational and vocational policy was unable to escape scepticism surrounding the EU." (authors' abstract; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; Berufsbildungspolitik; EU-Bildungspolitik; Europäische Integration; Vereinigtes Königreich